Workshop dan Edukasi “Perempuan Pakai Pembalut Kain” Remaja Putri Karanglo Sukoharjo Sleman: Indonesia - Hariyanti, Puji; Rumiani, Rumiani; Darmawan, Ibnu (UII, 2025)
Sanitary pad is a basic need for women who are reproductively active. At the same time, there are still many women who do not understand about menstrual health and hygiene and choose to use disposable sanitary pads. In fact, each woman can use more than 300 pads a year, depending on the duration and volume of bleeding. In the end, the sanitary pads waste will accumulate, because one sanitary pad takes 500-800 years to decompose. Furthermore, the usage of disposable sanitary pads is harmful to women's reproductive health. In this situation, women confront the negative stigma of contributing to waste while their health is jeopardized. As a result, this program, in collaboration with Biyung Indonesia, aims to provide a safe space for women to learn and discuss the right to healthy menstruation through three activity sessions: educational activities and workshops on making cloth sanitary pads, educational activities and workshops on making misting spray, and a social media campaign, which was attended by 25 Islamic boarding school students and young women, at Al Bayt Al Quran boarding school, Karanglo, Yogyakarta. This program successfully raised awareness and fostered active participation among participants in producing their own reusable menstrual pads, leading to healthier menstrual practices.